The Influence of Service Quality and Public Trust on Public Satisfaction in Using the Jakevo Application in Pulo Village, South Jakarta City - Samsudin; Sarah Suhalya (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the effect of service quality and public trust on public satisfaction in using the Jakevo application in Pulo Village, South Jakarta. The research method used is quantitative descriptive with multiple linear regression analysis techniques. A sample of 52 respondents was selected from the population of Jakevo application users in the period March 2023–March 2024. The results of the study show that service quality has a positive and significant effect of 60.5%, public trust has an effect of 77.5%, and both variables simultaneously affect public satisfaction by 79.5%. These findings reinforce the importance of service quality and trust as determinants of public satisfaction in digital government services.